PENGARUH ULASAN KONSUMEN DAN E-WOM DI PLATFORM E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN : STUDI SUNSCREEN AZARINE - Wilda Al Aluf; Setiyarini, Triana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the influence of consumer reviews and electronic Word of Mouth (e-WOM) on the purchasing decisions of Azarine sunscreen products on e-commerce platforms. The methodology used is quantitative research with a case study approach, involving 45 respondents who are students at Trunojoyo University Madura. The analysis results indicate that consumer reviews have a significant influence on purchasing decisions, while e-WOM does not show a meaningful impact individually. These findings provide insights into the importance of consumer reviews in shaping purchasing decisions and identify the need for further research to understand the dynamics of e-WOM in this context.